Cultura e imagem: o cinema neo-realista no Mercosul 1955 a 1962 - Tonetto, Maria Cristina (2006)
This paper of the Latin American Integration Master has approached the imaginary construction of a specific region in the MERCOSUL, through the films neorealists in the cinematography of Brazil and Argentina, in the period of 1955 the 1962. The answer for what we were looking for if the neo-realistic school had brought near to Brazil and Argentina movies and through which prism this similarity had happened. To answer these investigations we carry out a study, which emphasizes the relation between history, cinema and its ramifications, using some readings on the new concepts of historical inquiry, which opened the way for definitions of representation and imaginary. To complement this analysis an inquiry bibliography happened in Brazil and in Argentina, in Theories, Scientific Articles and movies of the analysed time, in Brazil, Rio, 40 Degrees, in Argentina, The flooded and in Italy, Thieves of Bicycle. The investigation of the selected material provided the knowledge of collective and individual data of the communities from the MERCOSUR and its cultural approximations. It showed a cinematographic approximation between Brazil and Argentina in the neo-realistic movies and its regional approach, which revealed the habits, customs and political and social inquiries from these countries. Our study revealed also the importance of the cinema as one more alternative in the creation of a cultural politicy into the MERCOSUR.